2019
DOI: 10.1093/pcp/pcz175
|View full text |Cite
|
Sign up to set email alerts
|

Different Plant Species Have Common Sequence Features Related to mRNA Degradation Intermediates

Abstract: mRNA degradation is an important cellular mechanism involved in the control of gene expression. Several genome-wide profiling methods have been developed for detecting mRNA degradation in plants and animals. However, because many of these techniques use poly (A) mRNA for library preparation, degradation intermediates are often only detected near the 3′-ends of transcripts. Previously, we developed the Truncated RNA End Sequencing (TREseq) method using Arabidopsis thaliana, and demonstrated that this method ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…In degradome analysis, the term “cleavage score” was used to estimate RNA cleavage efficiencies in previous studies (Anderson et al 2018; Ueno et al 2018). In this analysis, we defined cleavage score at the site level (CS site ) as the number of 5’ degradation intermediates normalized against RNA abundance (Ueno et al 2018, 2020). In addition, as with efficiencies of RNA cleavage at the gene level, we defined the sum of CS site values in each gene as the CS gene value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In degradome analysis, the term “cleavage score” was used to estimate RNA cleavage efficiencies in previous studies (Anderson et al 2018; Ueno et al 2018). In this analysis, we defined cleavage score at the site level (CS site ) as the number of 5’ degradation intermediates normalized against RNA abundance (Ueno et al 2018, 2020). In addition, as with efficiencies of RNA cleavage at the gene level, we defined the sum of CS site values in each gene as the CS gene value.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we discovered sequence motifs using sequences around (from − 10 to + 10), upstream (from − 20 to − 5), or downstream (from + 5 to + 20) of cleavage sites using DREME, and then used STAMP to carry out phylogenetic analyses based on similarities among the discovered motifs (Supplementary Figures S10–S12). We also obtained sequences around, upstream, or downstream of cleavage sites in different plant species ( Lactuca sativa [lettuce], Oryza sativa [rice], and Rosa hybrida [rose]) reported in a previous study (Ueno et al 2020), and added sequence motifs for phylogenetic analyses. Generally, similar G-rich sequence motifs were observed around the cleavage sites (from − 10 to + 10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process, the exon junction complex is removed thus keeping the mRNA stable and the rate of eRF1 synthesis high. After Nyikó et al (2017) mRNAs are also degraded co-translationally where the 5'-3' exoribonuclease XRN4 follows a ribosome, whether it is actively translating or stalled (Merret et al, 2015;Ueno et al, 2019;Ueno, Yamasaki, Demura, & Kato, 2018;X. Yu, Willmann, Anderson, & Gregory, 2016).…”
Section: Translation Reinitiationmentioning
confidence: 99%
“…P‐bodies also contain ribonucleases for RNA degradation. However, several recent studies have shown that mRNAs are also degraded co‐translationally where the 5'–3' exoribonuclease XRN4 follows a ribosome, whether it is actively translating or stalled (Merret et al, 2015; Ueno et al, 2019; Ueno, Yamasaki, Demura, & Kato, 2018; X. Yu, Willmann, Anderson, & Gregory, 2016). The evidence?…”
Section: The Plant Translation Apparatusmentioning
confidence: 99%